ASSESSMENT OF VITAMIN D AND CALCIUM LEVELS IN WOMEN WITH PCOS: AN OBSERVATIONAL STUDY - ARORA, SARU; KAUR, PARNEET; GARG, RAMA; KAUR, MANINDER; RANI, SANGEETA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Polycystic ovarian syndrome (PCOS) is a prevalent endocrinal disorder in the women of reproductive age group. The present study aims to investigate the correlation between Vitamin D and calcium levels in PCOS subjects as well as to establish the correlation between body mass index, hyperandrogenism, and metabolic syndrome in various phenotypes of PCOS. Methods: In the present prospective and observational study, a total of 80 patients diagnosed with PCOS were recruited. The recruited patients were divided in the following two groups - study group (60 women diagnosed with PCOS based on Rotterdam criteria); and control group (20 women without PCOS recruited from outpatient department and infertility clinics). Baseline characteristics, Vitamin D level, and serum calcium levels were measured in the two groups and then compared. Results: The mean age of patients in both the groups was found to be comparable (study group: 26.45±5.95 years versus control group: 28.40±6.65 years; p=0.221). The difference of mean 25-Hydroxy Vitamin D3 level was found to be statistically highly significant (study group 14.71 [±9.12] ng/mL versus control group was 22.47 [±6.71] ng/mL; p=0.0008). The difference of mean serum calcium level was also found to be statistically highly significant (study group 9.14 [±0.50] mg/mL, and control group 9.74 [±0.45] mg/mL; p<0.0001). Conclusion: Women with PCOS have a significantly lower serum 25-hydroxyvitamin D and calcium levels as compared to controls. There is need for routine Vitamin D3 and calcium screening in all patients of PCOS for better insight into its role in the syndrome. Screening and correction of Vitamin D3 and calcium deficiency may prevent PCOS and its manifestations.